2017
DOI: 10.1021/acs.jpcc.7b01136
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Mechanisms of α-Octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine Nanoparticles at High Temperatures

Abstract: Density functional tight-binding molecular dynamics simulations with dispersion corrections were performed to study the adiabatic initial decomposition processes of molecular explosive α-octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (α-HMX) nanoparticles (NPs) with the diameters of 1.4–2.8 nm at high temperatures from 2400 to 3000 K. The results indicate that the global thermal decompositions of the HMX NPs present great dependence on the temperature and particle size. The initial decomposition process of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…As illustrated in Table , the relative errors of densities of β-, ε-, and γ-CL-20 are 3.2, 3.8, and 4.7%, respectively, showing the reliability of the DFTB method applied to the three polymorphs of CL-20 at ambient condition. In combination with previous successful applications of the method on the decay mechanisms of EMs, such as HN 3 , TATB, HMX, TKX-50, and so forth, , we believe that our simulations of this work should be reliable.…”
Section: Results and Discussionsupporting
confidence: 61%
“…As illustrated in Table , the relative errors of densities of β-, ε-, and γ-CL-20 are 3.2, 3.8, and 4.7%, respectively, showing the reliability of the DFTB method applied to the three polymorphs of CL-20 at ambient condition. In combination with previous successful applications of the method on the decay mechanisms of EMs, such as HN 3 , TATB, HMX, TKX-50, and so forth, , we believe that our simulations of this work should be reliable.…”
Section: Results and Discussionsupporting
confidence: 61%
“…Three kinds of steps starting the decay of the HMX molecules are observed in our MD simulations of heating the three polymorphs, including the C–N bond breakage to open the ring­(I), the N–NO 2 fission­(II) and the secondary reaction between the intermediates and HMX reactants, or the intermediate-initiated decomposition­(III), as illustrated in Figure . These steps were also ascertained in previous work, and Reaction II was deemed dominant among all the possible steps. ,, Reactions I and II occur in all three polymorphs of HMX, and the partitioned NO 2 and the broken C–N bonds can be axial or equatorial. As exhibited in Figure , the energy barrier of the NO 2 partition depends on the extending orientation to a certain extent.…”
Section: Resultsmentioning
confidence: 86%
“…In previous studies, it was believed that the elimination of HONO is also one of the main initial thermal decomposition steps of HMX. [40][41][42]44,57,67,71,74 However, in our simulations, the HONO elimination has not been observed in a way of transferring the H atom of the CH 2 group to the O atom of -NO 2 to form a N−NO 2 H bond and simultaneously breaking it. By tracing the MD trajectories of our simulations, it is found that the HONO is formed by the reactions among the intermediate, such as H + NO 2 ⃗ HONO; meanwhile, it produces small molecular products by means of some reactions like HONO ⃗ HO + NO.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations